The (lack of) consequences of reasonable doubts on the independence of the judiciary system on cooperation in criminal matters in the EU1 - Dominika Czerniak (Revista Brasileira de Direito Processual Penal, 2022)
The article analyses the consequences of the violation of judicial independence in the cooperation in criminal matters. The right to an independent court is not only a fundamental value in the rule of law (Article 2 TEU, Article 19(1)), but also one of the fundamental rights (Article 47 CFR). Jeopardising the independence of the judiciary in one of the EU countries should have an impact on the possibility of cooperation in criminal matters. Leaving the standard of independence of the judiciary resulting from the ECHR jurisprudence, the article summarises the current jurisprudence of the CJEU concerning the independence of the judiciary and the impartiality of judges at two levels: general (or systemic), and in connection with the operation of the EAW. The article analyses present situation in Poland and recent judgments of the CJEU in “Polish cases” – about the problem of executing the EAW and evaluating the independence of the judiciary system in Poland.